2019
DOI: 10.1093/mnras/stz372
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-spherical collapse of matter in ΛCDM

Abstract: We report the findings of new exact analytical solutions to the cosmological fluid equations, namely for the case where the initial conditions are perturbatively close to a spherical tophat profile. To do so we enable a fluid description in a Lagrangian-coordinates approach, and prove the convergence of the Taylor-series representation of the Lagrangian displacement field until the time of collapse ("shell-crossing"). This allows the determination of the time for quasi-spherical collapse, which is shown to hap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Deviating from 1D, we have generically V eff = 0, and, as a result, the ZA performs rather poorly as gravitational tidal effects become non-negligible. In particular, this reflects in inaccurate predictions of the ZA for the shell-crossing time that worsen successively when deviating more and more from the 1D collapse [15][16][17]. Very similar performance issues are expected for the propagator method.…”
Section: Results Beyond 1d Collapsementioning
confidence: 78%
See 1 more Smart Citation
“…Deviating from 1D, we have generically V eff = 0, and, as a result, the ZA performs rather poorly as gravitational tidal effects become non-negligible. In particular, this reflects in inaccurate predictions of the ZA for the shell-crossing time that worsen successively when deviating more and more from the 1D collapse [15][16][17]. Very similar performance issues are expected for the propagator method.…”
Section: Results Beyond 1d Collapsementioning
confidence: 78%
“…The central quantity is the Lagrangian displacement field that encodes how fluid elements are displaced as a function of time and initial (Lagrangian) position. The corresponding perturbative framework is usually called Lagrangian perturbation theory (LPT), and, although a challenge, allows to investigate the instance of shell-crossing by analytic means [12][13][14][15][16][17]. However, to update the gravitational potential that is responsible for displacing the fluid elements, one still requires, effectively, the Eulerian density.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that, so far, the mathematical convergence of the SPT series until shell-crossing has not been explicitly demonstrated, except for the simplified cases of one-dimensional (McQuinn and White 2016) and spherical collapse (Rampf 2019). Nonetheless, convergence for cosmological initial conditions until-but excluding-shell-crossing is likely, mainly as a consequence of the analyticity results in Lagrangian coordinates Schmidt 2021).…”
Section: Perturbative Methods and Overview Of Applicationsmentioning
confidence: 94%
“…By applying equivalent multi-scaling techniques in Lagrangian coordinates as reviewed above, it has been shown that the matter collapse of arbitrary small departures from spherical symmetry also constitutes an exact solution of (19) until shellcrossing (Rampf 2019). In that case, the initial gravitational potential can be taken to be…”
Section: Analytical Shell-crossing Solutions For Simplified Initial Conditionsmentioning
confidence: 99%
“…Because they follow elements of fluid along the motion, Zel'dovich ap-proximation and higher-order LPT provide us with a rather accurate description of the large scale matter distribution, even in the nonlinear regime, shortly after shell crossing. The families of singularities that form at shell-crossing and after have been examined in detail in the Lagrangian dynamics framework (Arnold et al 1982;Hidding et al 2014;Feldbrugge et al 2018), and the structure of cosmological systems at shell-crossing has been investigated for specific initial conditions (Novikov 1969;Rampf & Frisch 2017;Saga et al 2018;Rampf 2019) and for random initial conditions ).…”
Section: Introductionmentioning
confidence: 99%